Oral Delivery of Astaxanthin via Carboxymethyl Chitosan-Modified Nanoparticles for Ulcerative Colitis Treatment - Wen Zhang; Xinping Zhang; Xinyi Lv; Ao Qu; Wenjing Liang; Limin Wang; Pei Zhao; Zijian Wu (Molecules, 2024)
The oral delivery strategy of natural anti-oxidant and anti-inflammatory agents has attracted great attention to improve the effectiveness of ulcerative colitis (UC) treatment. Herein, we developed a novel orally deliverable nanoparticle, carboxymethyl chitosan (CMC)-modified astaxanthin (AXT)-loaded nanoparticles (CMC-AXT-NPs), for UC treatment. The CMC-AXT-NPs were evaluated by appearance, morphology, particle size, ζ-potential, and encapsulation efficiency (EE). The results showed that CMC-AXT-NPs were nearly spherical in shape with a particle size of 34.5 nm and ζ-potential of −30.8 mV, and the EE of CMC-AXT-NPs was as high as 95.03%. The CMC-AXT-NPs exhibited preferable storage stability over time and well-controlled drug-release properties in simulated intestinal fluid. Additionally, in vitro studies revealed that CMC-AXT-NPs remarkably inhibited cytotoxicity induced by LPS and demonstrated superior antioxidant and anti-inflammatory abilities in Raw264.7 cells. Furthermore, CMC-AXT-NPs effectively alleviated clinical symptoms of colitis induced by dextran sulfate sodium salt (DSS), including maintaining body weight, inhibiting colon shortening, and reducing fecal bleeding. Importantly, CMC-AXT-NPs suppressed the expression of pro-inflammatory cytokines like TNF-α, IL-6, and IL-1β and ameliorated DSS-induced oxidative damage. Our results demonstrated the potential of CMC-modified nanoparticles as an oral delivery system and suggested these novel AXT nanoparticles could be a promising strategy for UC treatment.